Self‐organization of micro reinforcements and the rules of crystal formation in polypropylene nucleated by non‐selective nucleating agents with dual nucleating ability. Issue 6 (21st July 2020) - Menyhárd, Alfréd; Molnár, János; Horváth, Zsuzsanna; Horváth, Flóra; Cavallo, Dario; Polyák, Péter
Abstract: This work demonstrates and models the self‐organization of mixed polymorps in polymers containing simultaneously growing phases with different growth rates. The model was verified and demonstrated in isotactic polypropylene nucleated by a non‐selective nucleating agent. The crystallization and melting processes were studied by calorimetry (DSC) and polarized light microscopy (PLM). The morphology of the samples was investigated using PLM and scanning electron microscopy (SEM). The fundamental rules of the formation of two polymorphic modifications developing simultaneously on the same nucleating particle are introduced. A simple equation is suggested to predict the morphological geometry on the lateral surface of the nucleating agent. The results indicated good agreement between the predicted and observed geometry. The proposed model explains the self‐organization of micro‐sized reinforcements of α‐modification in the matrix of β‐iPP. Although the proposed equation was tested for this particular case it is a general equation for all structures in which different polymorphs are growing simultaneously with different growth rates. Abstract : This work presents a simple geometrical equation, which describes rules of crystal formation on a surface on which two polymorphic modification develop with different growth rates as well as the geometry of cross‐nucleation process. Such systems can form an interesting morphology in which the slower phase is occluded in the faster.